A Critical Legal Analysis of Occupational Health in Mining Sector in India with special reference to Difficulties and Challenges faced in Mining Sector - Adhav, Sunita (International Journal For Multidisciplinary Research, 2025)
Occupational health and safety of workers has always been an issue in different industrial sector. The researcher in this paper focuses on the health issues, safety performance and concerns of workers working in Mining sector in India. Further the researcher has covered the legal analysis on the same. The paper also talks about different challenges faced by workers in mining sector and the health risk involved in the same